The Effect of Comprehensive Sexuality Education (CSE) on Reducing Risky Sexual Behavior Among Adolescents - Nahdiyatul Mukaromah; Putri Amalia; Dyah Ayu Fitriani; Suci Gustia Saputri; Lukmi Wulandari (Rifa'Institute, 2025)
Introduction: Adolescents often face risky sexual behaviours due to limited knowledge and guidance. Comprehensive Sexuality Education (CSE) is a potential strategy to address this issue. Objective: To evaluate the effect of CSE on reducing risky sexual behaviour among adolescents in Bekasi District, Indonesia. Methods: A quasi-experimental design was used with 106 high school students divided into intervention and control groups. The intervention group received a four-session CSE program. Data were analysed using paired t-tests and Mann–Whitney U tests. Result and Discussion: The intervention group showed significantly higher post-intervention behaviour scores (M = 64.66) than the control group (M = 50.38), with p < 0.01. Conclusion: CSE effectively improves adolescent sexual behaviour. Integration of such programs is recommended in public health strategies targeting youth